A extens\~ao da cadeia produtiva da economia mineral no PIB brasileiro - Rafael Le\~ao; Rodrigo Rabelo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The extension of the mineral economy's value-chain is a relevant subject for the Brazilian debate on public policies for economic growth, but the numbers and definitions on the topic are still imprecise and, therefore, remain under construction. At first, based on the official classification of economic activities, a methodological discussion is presented to carefully establish the conceptual boundaries of the mineral economy, including the concepts of mining and transformation of minerals. In addition, a quantitative technique to precisely measure the extension of the mineral economy's value-chain and its linkages in Brazilian gross domestic product (GDP) is suggested. Finally, the paper presents the estimates considering Brazil's economic background over the last twenty years.
Keywords: C67; D57; L61; L72; Q33; 330; mineral economy; value chain; input-output matrix; value added; GDP